Development of SCAR marker for Phytophthora resistance in black pepper (Piper nigrum L.) - A Ishwara Bhat, R Suseela Bhai, M Anandaraj, Sheji Chandran, Renu Susan George, (Journal of Spices and Aromatic Crops, 2008)
Foot rot disease caused by Phytophthora capsici is one of the major production constraints inblack pepper (Piper nigrum) in India. RAPD profile of moderately resistant and susceptible linesindicated the presence a unique band of 360 base pair in moderately resistant lines with theprimer OPA-01. The DNA fragment associated with these lines was cloned, sequenced andconverted into a SCAR marker. The SCAR primer was tested on plants that were classified asmoderately resistant and susceptible. SCAR primers amplified DNA invariably from resistantplants only. The sequence of the unique band matched with stress related gene sequences reportedin several eukaryotes including Arabidopsis thaliana.